Inverse Projection Techniques
XII, 144 p.
Keywords: Inverse Projection is a method for estimating accurate demographic indicators of a population where vital registration data are available, but population censuses are lacking or unreliable. The book offers an overview of the present state of methodological development in the field of inverse projection techniques. In the various chapters of the book, leading experts in demography and related fields review the method, discuss recent extensions, test performances, and stress differences of the various procedures. The book is intended for all scientists who are interested in the reconstruction of demographic scenarios in particular situations, with specific kinds of data, as well as for statisticians and mathematicians who are attracted by this fascinating field of application.